Cytotoxicity of lipopolysaccharide extracted from Salmonella enterica serovar Typhimurium on Breast Cancer Cell Line mcf-7 - Wissam Qadry Mutaab Alqaissy1 , Aziz L.M.2 , Abdul-Rahman Ibrahim A.3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lipopolysaccharide was selected to investigate its effect on cell line of breast cancer in vitro, thereforelipopolysaccharide was extract from Salmonella enterica serovar Typhimurium followed by evaluation of itscytotoxicity. The experiment was divided into three parts. The first part included isolation and identificationof S. enterica serovar Typhimurium from 302 samples included 201diarrheic patient samples and 101 foodsamples of poultry meat and as well as the isolates identification on molecular level through used of threegenes (invA, STM4497 and Stn) genes detected using the technique of PCR, the results shown there wereseven bacterial isolates diagnosed as S. enterica serovar Typhimurium. The second part of the experimentwas extract of LPS from 10.66 g of dry weight of bacteria by hot phenol method. The concentration of LPSin phenolic phase was 435.57?g/ml while in aqueous phase was 381.76 ?g/ml. The LPS molecular weightwas estimate which was equivalent to 93325 for phenolic and 71614 Dalton for aqueous phases. The thirdpart of experiment was to study the effect of cytotoxicity in cell line of breast cancer by used differentconcentrations of lipopolysaccharide. Lipopolysaccharide showed cytotoxicity on the breast cancer cell linemcf-7 in both phenolic and aqueous phases of LPS. The results showed the highest rate of inhibition ofbreast cancer cells at the concentration of 350 ?g/ml by 61.67% in the phenolic phase while the rate ofinhibition was 53.33% in the same concentration of the aqueous phase.